2018
DOI: 10.4269/ajtmh.18-0077
|View full text |Cite
|
Sign up to set email alerts
|

Gametocyte Development and Carriage in Ghanaian Individuals with Uncomplicated Plasmodium falciparum Malaria

Abstract: gametocytes develop over 9-12 days while sequestered in deep tissues. On emergence into the bloodstream, they circulate for varied amounts of time during which certain host factors might influence their further development. We aimed to evaluate the potential association of patient clinical parameters with gametocyte development and carriage via in vivo methods. Seventy-two patients were enrolled from three hospitals in the Volta region of Ghana in 2016. Clinical parameters were documented for all patients, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…A large study by Nacher et al examined host factors influencing P. falciparum gametocyte carriage and found that hemoglobin concentrations (as a measure for anemia) were negatively correlated with peak gametocyte counts and gametocyte carriage duration (Nacher et al, 2002). This association between gametocytemia and anemia has been reported in other studies (Price et al, 1999;Stepniewska et al, 2008;Dinko et al, 2018), suggesting that anemia, and thus perhaps tissue hypoxia, stimulates P. falciparum gametocytogenesis. A large Nigerian study of 1125 children attempted to discern the mechanism by which anemia influences gametocyte development and found the proportion of male to female gametocytes in anemic children was nearly twofold higher than in non-anemic children.…”
Section: Hematocrit Levelsmentioning
confidence: 71%
See 1 more Smart Citation
“…A large study by Nacher et al examined host factors influencing P. falciparum gametocyte carriage and found that hemoglobin concentrations (as a measure for anemia) were negatively correlated with peak gametocyte counts and gametocyte carriage duration (Nacher et al, 2002). This association between gametocytemia and anemia has been reported in other studies (Price et al, 1999;Stepniewska et al, 2008;Dinko et al, 2018), suggesting that anemia, and thus perhaps tissue hypoxia, stimulates P. falciparum gametocytogenesis. A large Nigerian study of 1125 children attempted to discern the mechanism by which anemia influences gametocyte development and found the proportion of male to female gametocytes in anemic children was nearly twofold higher than in non-anemic children.…”
Section: Hematocrit Levelsmentioning
confidence: 71%
“…Lack of an acute infection could prevent gametocyte exposure to important damaging elements of the immune system, such as inflammatory cytokines (von Seidlein et al, 2001). A more recent study in Ghana identified relatively lower prevalence of gametocytemia in patients with fever (Dinko et al, 2018). In vitro findings demonstrated that increased levels of cytokines (including TNF-a and IFN-g) correlated with a lack of gametocyte infection of the mosquito vector (Naotunne et al, 1993).…”
Section: Immune Statusmentioning
confidence: 99%
“…Gametocytes are specialized sexual stages which mediates the transmission of malaria from humans to mosquitoes (Dinko et al 2018). The findings of this study showed that there was no significant difference on the appearance of gametocyte at baseline and carriage of baseline gametocyte between the two treatment groups.…”
Section: Discussionmentioning
confidence: 56%
“…The Plasmodium parasites are transmitted through the bite of infected female Anopheles mosquitoes (Essangui et al 2019), with the pathology resulting from the asexual replication of parasites within circulating red blood cells, leading to anemia, disrupted blood flow, and inflammation that can be lethal if untreated (Dinko et al 2018;Essangui et al 2019). Parasite invasion rate into erythrocytes is dependent on both erythrocyte blood group antigen and haemoglobin genotype as blood group O and B provided protection via reduced merozoite invasion in RBCs (Amoah et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sexually committed ring stage trophozoites from erythrocytic stages in peripheral circulation (9, 10) progress into gametocyte developmental stages 1 to IV while sequestered in bone marrow compartments (1114). This constitutes the main reason why only late gametocyte stages are found in peripheral circulation.…”
Section: Introductionmentioning
confidence: 99%